Arab Spring constitution-making: polarization, exclusion, and constraints. Issue 7 (9th November 2016) - Cross, Ester; Sorens, Jason
ABSTRACT: What determines the balance that democratizing constitutions strike between majority empowerment and individual rights? Some constitutions deliberately handicap state power to forestall threats to liberty, while others try to empower the government to hold the country together. We answer this question in the context of post-Arab Spring constitution-making, hypothesizing a U-shaped relationship between polarization among politically significant factions and net majority-empowering provisions in constitutions of new democracies, a relationship mediated by breadth of inclusion in the constitutional drafting process. We test the hypothesis through a controlled case comparison of Tunisia, Libya, and Egypt, the three Arab-majority countries in which protestors successfully toppled authoritarian regimes.